2019
DOI: 10.3390/bs9010007
|View full text |Cite
|
Sign up to set email alerts
|

Which Factors Influence Attentional Functions? Attention Assessed by KiTAP in 105 6-to-10-Year-Old Children

Abstract: This research revealed the children with difficulties in attentional functions among healthy children attending primary school and aimed to identify the possible sociodemographic factors, such as the child’s age, gender, and school grade, that could influence attentive performance. The participants were 105 children aged 6–10 years (M age = 8.6; SD = 1.04), attending primary schools. Family economic condition was mostly at a medium level (63.5%), and parents most frequently had 13 years of schooling. The compu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 52 publications
1
22
0
2
Order By: Relevance
“…Studies have shown that boys have lower attentional performance and poorer inhibitory control but perform faster than girls [50]. Consistent with these findings, we found that girls spent more time completing MEDAL (median 15 min per day vs 13 min per day), but they were more agreeable to the time spent on MEDAL compared with boys.…”
Section: Discussionsupporting
confidence: 89%
“…Studies have shown that boys have lower attentional performance and poorer inhibitory control but perform faster than girls [50]. Consistent with these findings, we found that girls spent more time completing MEDAL (median 15 min per day vs 13 min per day), but they were more agreeable to the time spent on MEDAL compared with boys.…”
Section: Discussionsupporting
confidence: 89%
“…Longitudinal studies examining the relationship between visual-motor skills and academic achievement demonstrate that third grade literacy [27], math and spelling scores [28] are predicted on the basis of early eye-hand coordination tasks. These results suggest that academic tasks and school demands require abilities to process visual clues, perceive spatial relations among objects and integrate visual information with fine finger movements to assure successful behaviors in the classroom and academic achievements [20,29].…”
Section: Handwriting and Academic Successmentioning
confidence: 88%
“…Numerous studies have analyzed the relationship between fine motor skills (hereafter FMS) and the main predictors of writing performances. Handwriting performance has been reported to be influenced from visual perception, eye-hand coordination, and visual-motor integration [9][10][11][12]. For example, previous studies investigating the association between visual-perception and handwriting outcomes have demonstrated that visual-motor integration is a significant component of writing performance [11,[13][14][15][16][17].…”
Section: Relationship Between Fine Motor Skills Eye-hand Coordinatiomentioning
confidence: 99%